Nurturing academic connections: Universiti Teknologi MARA Pulau Pinang Malaysia visit Universitas Negeri Malang Indonesia / Khairil Anuar Bahari ... [et al.] - Bahari, Khairil Anuar; Sh Abdul Nasir, Sh Firdaus; Sunaryo, Nony Aji; Normalasari, Riana (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
In a significant step towards fostering international academic collaboration, Universiti Teknologi MARA Pulau Pinang, Malaysia, embarked on a fruitful journey to Universitas Negeri Malang, Indonesia from September 13th to 16th, 2023. This visit aimed to promote educational exchanges, facilitate knowledge sharing, and enhance cooperation between the two esteemed institutions. The Malaysian delegation comprised of two accomplished lecturers from Universiti Teknologi MARA Pulau Pinang: En Khairil Anuar bin Bahari and Dr, Sh Firdaus bin Sh Abdul Nasir. They joined forces with their Indonesian counterparts, Nony Sunaryo and Riana Normalasari, from Universitas Negeri Malang. The primary objective of this visit was to establish a strong foundation for collaboration between the two universities. Both institutions recognized the potential for enriching their academic programs through joint efforts and knowledge sharing. The focus areas for discussion during this visit were culinary tourism and mechanical engineering, reflecting the strengths of both institutions in these fields.